Isolation-protocol, characterization, and in-vitro performance of equine umbilical vein endothelial cells - Lessiak, Ulrike; Melchert, Maria; Walter, Ingrid; Kummer, Stefan; Nell, Barbara; Tschulenk, Waltraud; Pratscher, Barbara (Frontiers in Veterinary Science, 2024)
Angiogenesis plays a crucial role in various physiological and pathological conditions. However, research in equine angiogenesis is relative limited, necessitating the development of suitable in-vitro models. To effectively analyze angiogenesis in-vitro, it is essential to target the specific cells responsible for this process, namely endothelial cells. Human umbilical vein endothelial cells (HUVECs) are one of the most used in vitro models for studying angiogenesis in humans. Serving as an equivalent to HUVECs, we present a comprehensive isolation protocol for equine umbilical vein endothelial cells (EqUVECs) with relatively minimal requirements, thereby enhancing accessibility for researchers. Umbilical cords obtained from five foals were used to isolate endothelial cells, followed by morphological and immunohistochemical identification. Performance of the cells in various assays commonly used in angiogenesis research was studied. Additionally, EqUVEC expression of vascular endothelial growth factor (VEGF) was assessed using ELISA. EqUVECs exhibited endothelial characteristics, forming a homogeneous monolayer with distinctive morphology. Immunohistochemical staining confirmed positive expression of key endothelial markers including von Willebrand factor (vWF), CD31, and vascular endothelial growth factor receptor-2 (VEGFR-2). Furthermore, performance assessments in in-vitro assays demonstrated the viability, proliferation, migration, tube formation and VEGF-expression capabilities of EqUVECs. The findings suggest that EqUVECs are a promising in-vitro model for studying equine angiogenesis, offering a foundation for further investigations into equine-specific vascular processes and therapeutic interventions.